OPTIMASI PRODUKSI KONVEKSI IZZA COLLECTION ANTARA DUA DESAIN T-SHIRT MENGGUNAKAN METODE PROGRAMA LINEAR DAN DISELESAIKAN DENGAN METODE SIMPLEX - Iqbal Apriza; Muhammad Fawwaz Izza, Martua Nehemia Sebastian, Paduloh (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
T-shirts are a timeless clothing model. American and British soldiers in the 19th century initially used T- shirts for their clothing. However, as time went by, T-shirts were also worn by the public for everyday wear and for less important events. Manufacturing plants that create t-shirt on a huge scale are by and large alluded to as ready-to-wear industrial facilities. Industry. Medium-sized confectionery companies usually have several constraints, such as: limited production materials, production capital, processing time, etc. This dairy portrays the endeavors of the confectionary industry in optimizing generatiom to attain greatest benefits with negligible exertion, without diminishing the quality of the products created. One way to achieve maximum benefit is to determine the production flow and limitations using linear programming. Linear programming is a solution technique for determining optimal resource allocation problems. The solution to this linear programming is supported by the Python application for Windows. This study reveals that with the given conditions and sales targets, maximum profit can be achieved by producing t-shirts